Probable Hydrocephalus Decompensation after Immunization with Pentavalent Vaccine: Case Report and Literature Review - Caixeta, Talles Henrique; Silva, Guilherme Júnio; Fursternau, Cristina Ribas; Amaral, Laurence Rodrigues (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
There are several complications associated with immunization with the pentavalent vaccine. Most of them are mild reactions, of spontaneous resolution; however, though rare, serious and potentially-fatal adverse effects can occur. We report a case of acute intracranial hypertension syndrome in an infant with a previously-unknown suprasellar arachnoid cyst who developed acute obstructive hydrocephalus after immunization with the pentavalent vaccine. He underwent neuroendoscopic treatment, showing complete resolution of the condition. The present article aims to compare the activation of the immune system by the pertussis component of the vaccine and the mechanisms that hypothetically potentiated the pathological decompensation.
Keywords: pentavalent vaccine; hydrocephalus; arachnoid cyst; inflammation; blood-cerebrospinal fluid barrier; neuroendoscopy